Pengaruh Harga, Kualitas Produk, Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan - Candra, Eko; Ketut Sunaryanto (Business and Investment Review, 2023)
Customer loyalty can be an effective, competitive and efficient strategy for a brand or company, because it can strengthen customer trust in the brand. Customers assess perceived loyalty based on price, product quality, service quality and satisfaction felt when shopping. The purpose of this study was to determine the effect of price, product quality, service quality, satisfaction and loyalty on customers who shop for material products in Indonesia. This research was conducted on 120 respondents located in Indonesia who are customers of material companies or stores. Data were collected using questionnaires distributed online and offline in July 2023. To test the research model, this study used SPSS 25. So that the following data were obtained: price, product quality, service quality and customer satisfaction have a joint effect on customer loyalty, price has a positive effect on customer loyalty, product quality has a positive effect on customer loyalty, service quality has a positive effect on customer loyalty, customer satisfaction has a positive effect on customer loyalty.